THE IMPLEMENTATION OF EXTENSIVE SPEAKING PROJECT AT STATE UNIVERSITY OF MAKASSAR - Suci Arnita Rahim; Chairil Anwar Korompot; Abdul Halim (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Even though the learning environment is still an online class, the implementation of the extensive speaking project is good and also in accordance with the actual method. In a semester, students work on two types of projects: group projects and individual projects. The lecturer allows students to choose their own topics, and students' project-related activities are conducted more outside of the classroom. Students' learning experiences in implementing large speaking projects were also reflected in numerous indicators in this study. These indicators include benefits such as strengthening students' public speaking skills and assisting them in being more critical thinkers, and also increased motivation and speaking fluency. Extensive speaking projects can contribute to developing students' abilities to be more creative, independent, collaborative, communicative, and technological. The project can also promote vocabulary knowledge, practice pronunciation, acquaint students with conveying ideas by extending the topic, and build students' self-confidence in the area of oral communication. As a result, they will be able to speak effectively and openly. The other indicator is the difficulties that students face in conducting extensive speaking projects, such as online learning, which renders the method less than optimally implemented.